1982
DOI: 10.1099/0022-1317-58-2-361
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection with Infectious Pancreatic Necrosis Virus Mediated by Defective-interfering (DI) Virus Particles in a Cell Line Showing Strong Interference but Little DI Replication

Abstract: SUMMARYThe characteristics of chinook salmon embryo cells persistently infected with infectious pancreatic necrosis virus were consistent with defective-interfering (DI) particle-mediated persistence. All the cells were infected and were slowly releasing virus, but they could be cured of virus in the presence of antiserum. Immunofluorescence showed that the amount of virus antigen in persistently infected cells was low. This fact, coupled with the observation that few DI particles were released by these cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In accordance with result reported earlier [17] cell culture supernatant from the persistently infected cultures were infective to freshly prepared cultures of CHSE cells. Extracellular virus could be detected at a concentration of approx.…”
Section: Virus Load In Persistently Infected Cells and In Infected Fishsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with result reported earlier [17] cell culture supernatant from the persistently infected cultures were infective to freshly prepared cultures of CHSE cells. Extracellular virus could be detected at a concentration of approx.…”
Section: Virus Load In Persistently Infected Cells and In Infected Fishsupporting
confidence: 92%
“…The mechanism behind a persistent infection in vitro is to a large extent unknown. It has been proposed that formation of defective interfering (DI) particles is one possible explanation while others have found that CHSE cells to a little extent supported the replication of DI particles [17]. Obviously, persistently infected cells have activated responses to suppress the viral load which is balanced against the replication rate of the virus, thus keeping the number of virus particles low.…”
Section: Introductionmentioning
confidence: 99%
“…While the general understanding would be that naked viruses release their progeny through cell lysis (38), our findings support virus release occurring without CPE being found by visual inspection of the cell cultures. This observation is not unique, and release of another fish pathogenic virus, infectious pancreatic necrosis virus, into cell culture supernatants at high copy numbers without obvious CPE has been observed (19,22). Further, release of rotavirus from polarized epithelial cells in vitro has also been observed to occur without cell lysis (17).…”
mentioning
confidence: 99%
“…Several studies indicated that marine bivalves are also common hosts of IPNV (Dobos et al, 1979;Lo et al, 1988 , 1978;Kennedy and MacDonald, 1982;Lo et al, 1990;MacDonald, 1978;MacDonald and Kennedy, 1979;MacDonald and Yamamoto, 1978;Malsberger and Cerini, 1963;Nicholson and Dunn, 1974). Most of the above studies indicated that defective interfering (DI) par ticles were involved in IPNV viral interference.…”
Section: Infectious Pancreatic Necrosis Virus (Ipnv) Ismentioning
confidence: 99%